Active Experiencing Training Improves Episodic Memory Recall in Older Adults - Banducci, Sarah E.; Daugherty, Ana M.; Biggan, John R.; Cooke, Gillian E.; Voss, Michelle; Noice, Tony; Noice, Helga; Kramer, Arthur F. (Frontiers in Aging Neuroscience, 2017)
Active experiencing is an intervention aimed at attenuating cognitive declines with mindfulness training via an immersive acting program, and has produced promising results in older adults with limited formal education. Yet, the cognitive mechanism(s) of intervention benefits and generalizability of gains across cognitive domains in the course of healthy aging is unclear. We addressed these issues in an intervention trial of older adults (N = 179; mean age = 69.46 years at enrollment; mean education = 16.80 years) assigned to an active experiencing condition (n = 86) or an active control group (i.e. theatre history; n = 93) for 4 weeks. A cognitive battery was administered before and after intervention, and again at a 4-month follow-up. Group differences in change in cognition were tested in latent change score models. In the total sample, several cognitive abilities demonstrated significant repeated-testing gains. Active experiencing produced greater gains relative to the active control only in episodic recall, with gains still evident up to 4 months after intervention. Intervention conditions were similar in the magnitude of gains in working memory, executive function, and processing speed. Episodic memory is vulnerable to declines in aging and related neurodegenerative disease, and active experiencing may be an alternative or supplement to traditional cognitive interventions with older adults.